Eurasianism in Turkey - Suat Kınıklıoğlu (Stiftung Wissenschaft und Politik (SWP), 2022)
Turkey's neo-Eurasianist ideologues describe themselves as 'Kemalist Eurasianists'. They argue that 'Eurasianism calls for a cultural, military, political and commercial alliance with Turkey's eastern neighbors, notably Russia, Iran, the Turkic countries of Central Asia, and even Pakistan, India and China' and is 'hostile towards any type of pro-Western policy in the Eurasian space. Turkey's neo-Eurasianists transformed from incarcerated villains to coalition partners in government and the bureaucracy. This spectacular reversal of fortunes could only materialize due to the special circumstances that arose from the ruthless power struggle between Turkey's Islamists. Nationalist-Islamism and Eurasianism overlap as they both despise Western dominance in the international order, feel threatened by the liberal cultural-civilizational siege of the West and thus have a common counter-hegemonic view of the world. Turkish Islamists and Eurasianists believe that a post-Western world is in the making. They argue that the unipolarity of the 1990s is over and that the West is essentially in an unstoppable decline - not least because of its degeneration in values. The true significance of Turkish 'Eurasianism' does not lie in its capacity to shape foreign and security policy although that cannot be totally disregarded; rather, its real contribution to the current regime comes from its critical role in widening and solidifying consent to authoritarian rule in Turkey.
Keywords: 320